An application of pursuit-evasion games in a missile guidance system - Salimi, Mehdi; Ibragimov, Gafurjan; Ismail, Fudziah (Pushpa Publishing House, 2010)
In this paper, the stroke between missiles (pursuer and evader) is considered. We construct a strategy for the pursuer that guarantees capturing the evader at time θ. This is done by providing an explicit formula for the strategy of the pursuer.